Determination of porcine derived components in gelatin and gelatin-containing foods by high performance liquid chromatography-tandem mass spectrometry. (January 2023) - Zhu, Xiaoyan; Gu, Shuqing; Guo, Dehua; Huang, Xinxin; Chen, Niannian; Niu, Bing; Deng, Xiaojun
Abstract: Detection and quantitation of porcine derived components in bovine and donkey gelatins and gelatin-containing foods is required for religious practices and consumer economic interests. In this study, shot-gun proteomics approaches were implemented to identify species-specific peptide biomarkers of three main gelatin origins, including porcine, bovine and donkey. Tryptic gelatin peptides were separated and analyzed with ultra-performance liquid chromatography-tandem high-resolution mass spectrometry (UPLC-HRMS), and 11 peptide biomarkers were selected for porcine, bovine and donkey. The gelatin pretreatment methods in three different food matrixes were optimized, and a label-free quantitative method using the MRM method of the most sensitive biomarker peptides was established. Among them, two porcine gelatin quantitative peptides were confirmed to have good linearity. The method has been successfully applied to the adulteration detection of porcine-derived components in gelatin and the quantification of porcine gelatin in candy and dairy products, with LODs of 0.07, 0.08 and 0.12 mg/kg, respectively. Graphical abstract: Image 1 Highlights: A strategy for identification of peptide biomarkers of common gelatin species was established. Eleven species-speciﬁc peptide biomarkers were selected for porcine, bovine and donkey gelatin. The pretreatment method has been optimized, especially for gelatin in dairy products. The quantitative method has been applied for adulterated porcine gelatin detection with good performance.